Latent tuberculosis co-infection is associated with heightened levels of humoral, cytokine and acute phase responses in seropositive SARS-CoV-2 infection. Issue 3 (September 2021) - Rajamanickam, Anuradha; Kumar, Nathella Pavan; Padmapriyadarsini, Chandrasekaran; Nancy, Arul; Selvaraj, Nandhini; Karunanithi, Kushiyasri; Munisankar, Saravanan; BM, Shrinivasa; Renji, Rachel Mariam; Ambu, T.C.; Venkataramani, Vijayalakshmi; Babu, Subash
Highlights: LTBI#x002B; and seropositive for SARS-CoV-2 infected individuals were associated with elevated IgM, IgG and IgA antibody titres. LTBI#x002B; and seropositive for SARS-CoV-2 infected individuals were associated with enhanced neutralization activity. LTBI#x002B; individuals exhibited significantly elevated plasma levels of cytokines, chemokines and acute phase responses. Our study clearly indicates the impact of LTBI on the humoral and innate immune responses in SARS-CoV-2 infection. Summary: Objectives: Latent Tuberculosis infection (LTBI) is postulated to modulate immune responses and alter disease severity in SARS-CoV-2 co-infection. However, no data exist on the effect of LTBI on the immune responses in SARS-CoV-2 co-infected individuals. Methods: We examined the SARS-CoV-2 specific antibody responses, plasma cytokines, chemokines, acute phase proteins and growth factor levels in LTBI positive and negative individuals with SARS-CoV-2 infection. Results: Our results demonstrated that individuals with LTBI (LTBI+) and seropositive for SARS-CoV-2 infection were associated with elevated SARS-CoV-2 specific IgM, IgG and IgA antibodies, as well as enhanced neutralization activity compared to those negative for LTBI (LTBI-) individuals. Our results also demonstrate that LTBI+ individuals exhibited significantly higher plasma levels of IFNγ, IL-2, TNFα, IL-1α, IL-1β, IL-6, IL-12, IL-15, IL-17, IL-3, GM-CSF, IL-10, IL-25, IL-33, CCL3 and CXCL10 compared to LTBI- individuals. Finally, our results show that LTBI+ individuals exhibit significantly higher levels of C-reactive protein, alpha-2 macroglobulin, VEGF and TGFα compared to LTBI- individuals. Conclusions: Thus, our data clearly demonstrates that LTBI+ individuals seropositive for SARS-CoV-2 infection exhibit heightened levels of humoral, cytokine and acute phase responses compared to LTBI- individuals. Thus, LTBI is associated with modulation of antibody and cytokine responses as well as systemic inflammation in individuals seropositive for SARS-CoV-2 infection.